Ten Principles of Interactional Communication Skills Implementation in Learning: The Case of Mahad As-salam Qur'anic Boarding School - Purnomo, Agustina Multi (Jurnal Sains Sosio Humaniora, 2023)
Communication skills in building an interactional atmosphere or interactional competence are future research in improving learning quality. The learning process in pesantren was usually one-way from the teacher to the students. This study aims to elaborate on applying ten principles for future research on interactional communication skills in the learning process at Mahad Assalam Qur'anic Boarding School. The analysis used qualitative methods. The data collection techniques were document studies, interviews, and observations. The results indicated that Mahad Assalam Qur'anic Boarding School had not fully implemented the ten interactional skills. The weakness was the management's lack of transparency regarding standard operating procedures, causing this research to be unable to confirm between interview data and the written documents. Non-disclosure regarding formal operating procedures documents can cause obstacles in applying the same standards and replicating learning methods. Interactional communication between teachers and students in the learning process and interpersonal relationships have been established. This finding allowed the continuation of the implementation of interactional communication skills after the learning process.